Resveratrol preserves the function of human platelets stored for transfusion. (18th December 2015) - Lannan, Katie L.; Refaai, Majed A.; Ture, Sara K.; Morrell, Craig N.; Blumberg, Neil; Phipps, Richard P.; Spinelli, Sherry L.
Summary: Stored platelets undergo biochemical, structural and functional changes that lead to decreased efficacy and safety of platelet transfusions. Not only do platelets acquire markers of activation during storage, but they also fail to respond normally to agonists post‐storage. We hypothesized that resveratrol, a cardioprotective antioxidant, could act as a novel platelet storage additive to safely prevent unwanted platelet activation during storage, while simultaneously preserving normal haemostatic function. Human platelets treated with resveratrol and stored for 5 d released less thromboxane B2 and prostaglandin E2 compared to control platelets. Resveratrol preserved the ability of platelets to aggregate, spread and respond to thrombin, suggesting an improved ability to activate post‐storage. Utilizing an in vitro model of transfusion and thromboelastography, clot strength was improved with resveratrol treatment compared to conventionally stored platelets. The mechanism of resveratrol's beneficial actions on stored platelets was partly mediated through decreased platelet apoptosis in storage, resulting in a longer half‐life following transfusion. Lastly, an in vivo mouse model of transfusion demonstrated that stored platelets are prothrombotic and that resveratrol delayed vessel occlusion time to a level similar to transfusion with fresh platelets. We show resveratrol has a dual ability to reduce unwanted platelet activation during storage, while preserving critical haemostatic function.